1995
DOI: 10.1097/00005392-199511000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rigiscan and Sleep Laboratory Nocturnal Penile Tumescence in the Diagnosis of Organic Impotence

Abstract: RigiScan is a useful tool for measuring nocturnal penile tumescence. However, base measurements are more accurate than tip measurements for evaluating erectile function. The currently accepted level of rigidity used to define a normal erection (70% or greater) overestimates organic erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Munoz and colleagues studied 17 patients with ED using NPT monitoring and noted that RigiScan underestimated rigidity at low levels [34]. In contrast, Licht and colleagues found that the RigiScan did not correlate with axial rigidity measurements at high levels of rigidity [42]. Other researchers measured the axial and radial rigidity in patients with ED and found a strong correlation between base rigidity and buckling pressure; however, tip rigidity measurement correlated poorly with axial measurements [33].…”
Section: Nocturnal Penile Tumescence (Npt) Testingmentioning
confidence: 99%
“…Munoz and colleagues studied 17 patients with ED using NPT monitoring and noted that RigiScan underestimated rigidity at low levels [34]. In contrast, Licht and colleagues found that the RigiScan did not correlate with axial rigidity measurements at high levels of rigidity [42]. Other researchers measured the axial and radial rigidity in patients with ED and found a strong correlation between base rigidity and buckling pressure; however, tip rigidity measurement correlated poorly with axial measurements [33].…”
Section: Nocturnal Penile Tumescence (Npt) Testingmentioning
confidence: 99%
“…Indeed, fragmentation of REM sleep is generally associated with poorly maintained erections, reflecting the instability of the pro-erectile stimulus. All validation studies of the RigiScan screening device that have included polysomnography eliminated subjects with REM suppression secondary to any cause [40,42]. These "validation" studies have essentially "cherry picked" patients who have good (ie, normal) REM sleep.…”
Section: Patients With Apparent Abnormal Findings Using Home Erectionmentioning
confidence: 99%
“…25 According to Licht et al, base rigidity is also more accurate than tip measurements to evaluate erectile function. 26 2) Patients with lung involvement were not withdrawn from study because pulmonary abnormalities occur in approximately 90% of adults with SCD. 27 The percent of lung involvement and hydroxyurea treatment was similar in the 2 groups.…”
Section: Discussionmentioning
confidence: 99%